Pengaruh Stres Kerja dan Persepsi Karyawan tentang Kepemimpinan terhadap Psychological Well-Being di PT. X Cimahi - Rissal Risyandi; Pras Rendy (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Job stress and leadership perception are critical factors influencing employees’ psychological well-being, particularly in the manufacturing sector characterized by high work demands. The main problem addressed in this study is how job stress and employees’ perceptions of leadership are related to psychological well-being among employees at PT X Cimahi. This study aims to analyze the relationship between job stress, leadership perception, and employees’ psychological well-being. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 100 employees of PT X Cimahi selected using purposive sampling. Descriptive analysis and Spearman’s Rho correlation were applied due to the non-normal distribution of the data. The results reveal a very strong and significant positive relationship between job stress and psychological well-being, indicating that job stress in this context functions as eustress rather than distress. In addition, a weak but significant negative relationship was found between leadership perception and psychological well-being. These findings suggest that job characteristics and production demands play a more dominant role in shaping employees’ psychological well-being than leadership perception alone within the manufacturing work environment.